Thermovoltage of tool work thermocouple and the tool wear in face milling - Kovač, Pavel; Milikić, Dragoje (Journal of Production Engineering, 1986)
Face milling experiments have been performed to investigate the thermovoltage of tool work thermocouple. The investigation have been performed with the three different values of cutting speed. During the thermovoltage measurement the tool wear was observed until the tool was worn